Improving the tea withering process using ethylene or UV-C - Alamar, M. Carmen; Terry, Leon A.; Collings, Emma R.; Thompson, Andrew J.; Mohareb, Fady R.; Kourmpetli, Sofia; Kevei, Zoltan; Bogaerts Marquez, Maria (Cranfield University, 2021)
The data set contains objective colour, respiration rate, water loss data, as well as individual catechin and theobromine concentrations of Camellia sinensis shoots subjected to UV-C radiation and ethylene supplementation during simulated withering.
Keywords: Camellia sinensis var'; 'transcriptome'; 'catechin'; 'theaflavin'; 'abscisic acid'; 'polyphenols'; 'Plant Physiology'; 'Post Harvest Horticultural Technologies (incl. Transportation and Storage)'